2015
DOI: 10.1016/j.bcp.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Interference with distinct steps of sphingolipid synthesis and signaling attenuates proliferation of U87MG glioma cells

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 69 publications
2
39
0
1
Order By: Relevance
“…In addition, it has been reported that the inhibition of sphingolipids by myriocin in glioma cells attenuates proliferation (Bernhart et al 2015). Our results are in line with these observations, suggesting an important role for sphingolipids in cell cycle progression.…”
Section: Figuresupporting
confidence: 92%
“…In addition, it has been reported that the inhibition of sphingolipids by myriocin in glioma cells attenuates proliferation (Bernhart et al 2015). Our results are in line with these observations, suggesting an important role for sphingolipids in cell cycle progression.…”
Section: Figuresupporting
confidence: 92%
“…Conversely, statins have been previously reported to prolong the survival and decrease the incidence of patients with various cancers (30)(31)(32). The mechanism of the anticancer activity of statins remains unclear, but a previous review has demonstrated this anticancer effect (33). Mitogen-activated protein kinase and extracellular signal-regulated kinase upregulate antiapoptotic molecules in small cell lung cancer (SCLC) cells (34,35), and simvastatin Table III.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous in vitro studies have demonstrated that statins arrest cells in the G1 or S phase by affecting cell-cycle regulatory proteins such as cyclins, cyclin-dependent kinases (CDKs), and inhibitors of CDK (33,41,42). In addition, statins have been considered to lead to apoptosis of cancer cells through effects of various molecules such as B cell lymphoma (Bcl)-2, Bcl-2-associated X protein and caspase 3 (33,(43)(44)(45). Furthermore, statins have been demonstrated to inhibit intracellular signaling pathways in cancer cells (33).…”
Section: Univariate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Erre mutatunk be néhány példát az 1. táblázatban [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: öSszefoglaló Közleményunclassified